INDIVIDUAL FACTORS AFFECTING THE SURVIVAL OF PATIENTS UNDERGOING HEMODIALYSIS (Global Conference on Medical and Health Sciences, 2026)
During follow-up, it was observed that not all studied parameters were available for every patient undergoing maintenance hemodialysis. Considering this limitation, receiver operating characteristic (ROC) analysis was performed to evaluate the impact of individual demographic and clinical factors—such as age, sex, comorbid conditions, dialysis-related characteristics, and vascular access type—on patient survival. ROC curves for individual predictors are presented in Figure 1.The analysis demonstrated that missed dialysis sessions, chronic heart failure, and the use of a central venous catheter were the strongest negative predictors of survival, showing the highest prognostic performance. Several other factors exhibited moderate predictive ability. These findings are consistent with previously published data on survival determinants in hemodialysis populations [3, 9].
Keywords: hemodialysis; survival; ROC analysis; comorbidities; dialysis adherence; vascular access; prognosis.